Penerapan Hukmum Weibull Pada Meitode Neiw Jersey Dalam Penenituan Cadangan Premi Asuransi Dwilguna Status Joilnt Life - rahma widia; muhammad subhan (Journal of Mathematics UNP, 2019)
Abstract— Life insurance company often find difficulties in decent money payment as according to agreement of claim. So, it is very important for the company to prepare everything to deal with this. The way is to allocate premium reserves using the New Jersey method. The calculation of endowment life insurance reserve by determining beforehand annuity, single premium, and annual premium using Weibull law. Based on the result of premium reserve calculation, the premium reserve value obtained at the end of the first year until the following year has increased. Keywords—Endowment Life Insurance, Premium Reserve, New Jersey Method, Weibull Law.